APOA5 rs651821 confers increased risk for hypertension in Tongdao Dong population. (2nd January 2020) - Wang, Haiying; Zhou, Taimei; He, Huiying; Peng, Rong; Wang, Sujie; Jiang, Xinglin
ABSTRACT: Hypertension is a complex disease that partially influenced by genetic factors. Up till now, the association between the rs651821 in apolipoprotein A5 (APOA5) gene and hypertension remains unknown. This study was undertaken to investigate the relationship between the APOA5 rs651821 and hypertension in Tongdao Dong population. A total of 274 participants were involved in this study (135 hypertensive patients and 139 nonhypertensive adults). The single nucleotide polymorphism (SNP) was genotyped by using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP). The results showed that the genotypic and allelic frequencies of rs651821 were significantly different between the normotensives and hypertensive subjects ( P = 0.009, P = 0.003 respectively). TC/CC genotypes of rs651821 were associated with an elevated risk of hypertension (TC/CC vs. TT: adjusted odds ratio (AOR) = 1.791, 95%CI = 1.067–3.006, P = 0.009). Besides, the TC/CC genotypes were related to an increased plasma triglyceride (TG) level (TC/CC vs. TT: 2.47 ± 1.91 vs. 1.82 ± 1.07, P = 0.001).The results suggest that the C carriers of APOA5 rs651821 are associated with an increased serum TG concentration and may cause the increased susceptibility of the individual to hypertension in Chinese Dong population.